Safe Food Handling Knowledge, Attitude and Practice of Food Handlers in Hospital Kitchen - Daru Lestantyo; Adi Heru Husodo; Susi Iravati; Zahroh Shaluhiyah (Intelektual Pustaka Media Utama, 2017)
Hospital food hygiene plays an important role to patient's health. Studies proved that improper practices and lack of knowledge are contributing factors of foodborne diseases. This study was conducted to determine knowledge, attitude and practice of hospital safe food handling in Semarang, Central Java. A cross sectional study was conducted in two general hospitals' kitchen. Data were collected from 60 food handlers through validated questionnaire. Respondents were grouped into two categories: a. Teaching Hospital, and b.Non-teaching Hospital. Data were collected in February-April 2017. Most of food handlers (80%) were graduated from vocational senior high school (SMK). Respondent's age were 28-37 years (36.7%) in average. Most of respondent‟s work experience (85%) was less than 15 years. The result showed that more than 80% of food handlers have good knowledge in safe food handling procedures, good attitude (66%) and good practices (90%). There was no significant difference of knowledge, attitude and practices between two groups. Results strongly emphasize the need of food hygiene training of hospital food handlers. It also suggest that non food handlers such as nurse or kitchen supervisor should involved in the training. Some aspects of food handlers' safety behavior need to be emphasized.